THE EFFECT OF OWNERSHIP STRUCTURE ON EARNINGS MANAGEMENT IN BANKING COMPANIES - Muqmainnah Musma; Hamzah Achmad; Nurina Saffanah (Jurnal Manajemen Sains dan Organisasi, 2024)
Objectives – This study aims to determine the effect of ownership structure on earnings management in banking companies. Design/Methodology/Approach – The population of this study are banking companies listed on the Indonesian Stock Exchange period 2019-2023. Sampling was carried out using a purposive sampling technique with certain criteria and a sample of 10 banking companies. The data analysis method used in this research is multiple linear regression. Findings – The results of this research show that institutional ownership has a positive and significant effect on earnings management. Managerial ownership has a positive and significant effect on earnings management. Conclusion and Implication – Institutional and managerial ownership has a positive and significant effect on earnings management. Investors who wish to purchase shares should first consider the company information. For companies, it is necessary to provide complete financial information and as a source of information regarding the company's financial condition by external parties as a consideration before making an investment.